2018
DOI: 10.1177/0748233718761698
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of two major phenolic compounds from the family Lamiaceae plants on the human gastric carcinoma cells

Abstract: Phenolic compounds of essential oils from the family Lamiaceae are commonly used substances in the food industry because of their flavouring, antimicrobial and antioxidant properties. In this context, it has become important to have healthy and safe products for consumers who are exposed to these phenolic compounds. The present study was aimed to investigate the toxic effects of carvacrol, thymol and their mixture on human gastric carcinoma (AGS) cells. Cells were analyzed after 24 h of exposure to different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…A positive correlation was found among cell death and ROS production after 24 h of exposure to thymol at higher doses, whereas a negative correlation was observed between cell death and GSH levels. These findings are in agreement with earlier reports [11,[13][14][15]. It is noteworthy to mention that in the present study, low doses of thymol induced the increased proliferation of healthy human fibroblasts as compared to unexposed control cells.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A positive correlation was found among cell death and ROS production after 24 h of exposure to thymol at higher doses, whereas a negative correlation was observed between cell death and GSH levels. These findings are in agreement with earlier reports [11,[13][14][15]. It is noteworthy to mention that in the present study, low doses of thymol induced the increased proliferation of healthy human fibroblasts as compared to unexposed control cells.…”
Section: Discussionsupporting
confidence: 94%
“…Another study focused on in vivo passage kinetics and has evidenced thymol metabolization in the stomach or intestine after an oral application [22]. Our research recently revealed that human gastric adenocarcinoma (AGS) cells are highly sensitive to thymol in a concentration-dependent manner [14,15]. Given those studies, it is of great interest to elucidate in depth whether thymol may have therapeutic potential against e.g., gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the Inula metabolites tested were sesquiterpenolides. On the other hand, thymol and thymol derivatives as well as extracts and essential oils containing these compounds [61][62][63][64] are known to be cytotoxic. These results suggest that the H extract induced a significant activation of a p21-dependent, p53-independent pathway in OCI-AML3 cells and that compound 2 was responsible of this activity and the associated cell cycle arrest.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the Inula metabolites tested were sesquiterpenolides. On the other hand, thymol and thymol derivatives as well as extracts and essential oils containing these compounds [61][62][63][64] are known to be cytotoxic.…”
Section: Resultsmentioning
confidence: 99%
“…Biological studies on this plants have reported anti-inflammatory [ 12 ], antiallergic [ 13 ], antioxidant effect [ 14 ] and also the possibility for zootechnical and reproductive medicine applications [ 15 ]. Lamiaceae exhibits cytotoxic and apoptotic effects on human cervical carcinoma (HeLa) and human breast cancer (MCF-7) cell lines [ 16 ] and gastric carcinoma cells [ 17 ]. O. sanctum Linn.…”
Section: Introductionmentioning
confidence: 99%